2012
DOI: 10.1177/0022034512446342
|View full text |Cite
|
Sign up to set email alerts
|

Association among Vitamin D, Oral Candidiasis, and Calprotectinemia in HIV

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…The other predisposing factors for candidiasis in this group included a decrement in the salivary concentration of the antimicrobial peptide calpronectin, the adverse effect of antiviral drugs and some specific sexual practices and habits. In the study by Sroussi et al (2012) a CD4 lymphocyte count \200 and vitamin D deficiency appeared to be the most crucial environmental factors leading to candidiasis in HIV-positive subjects.…”
Section: Periodontitismentioning
confidence: 91%
See 1 more Smart Citation
“…The other predisposing factors for candidiasis in this group included a decrement in the salivary concentration of the antimicrobial peptide calpronectin, the adverse effect of antiviral drugs and some specific sexual practices and habits. In the study by Sroussi et al (2012) a CD4 lymphocyte count \200 and vitamin D deficiency appeared to be the most crucial environmental factors leading to candidiasis in HIV-positive subjects.…”
Section: Periodontitismentioning
confidence: 91%
“…In an in vitro study Tang et al (2013) demonstrated that vitamin D reduced periodontitis related to Porphyromonas gingivalis by the inhibition of IL-8 expression in periodontal ligament cells. Sroussi et al (2012) showed that vitamin D deficiency in HIV-positive patients increased the risk of oral candidiasis. This opportunistic infection develops as a result of Arch.…”
Section: Periodontitismentioning
confidence: 99%
“…Oral candidiasis occurs by the combination of host, fungal, and oral microenvironment-modifying factors. A relationship between vitamin D defi ciency and oral candidiasis has been observed in HIV-infected patients; however, this relationship was not dependent on the number of CD4 + T lymphocyte cells (13) .…”
mentioning
confidence: 96%
“…), is also linked to vitamin D defi ciency (13) . Oral candidiasis occurs by the combination of host, fungal, and oral microenvironment-modifying factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation